Imported Dengue Fever in Tuscany, Italy, in the Period 2006 to 2012. Issue 5 (September 2014) - Lagi, Filippo; Zammarchi, Lorenzo; Strohmeyer, Marianne; Bartalesi, Filippo; Mantella, Antonia; Meli, Massimo; Blanc, Pierluigi; Tacconi, Danilo; Farese, Alberto; Zanelli, Giacomo; Pippi, Francesco; Aquilini, Donatella; et al.
<x xml:space="preserve">Abstract</x> This report focuses on epidemiological and clinical features of dengue fever (DF) in Tuscany (Italy) between 2006 and 2012. Sixty‐one DF cases were diagnosed, 32 of which were in the period of Aedes albopictus activity. Some clinical (arthralgia/myalgia, nausea/vomiting, and skin rash), laboratory (leukopenia and thrombocytopenia), and epidemiological characteristics (travel in a continent other than Africa) significantly distinguished DF cases from other febrile illnesses. Our data stress the importance of increasing awareness on dengue in Italy among clinicians in order to reach an early diagnosis in returning travelers and to implement appropriate clinical and public health interventions.